Prevalence and severity of restless leg syndrome in patients with spinal cord injuries - Gillani, Syed Faraz Ul Hassan Shah; Iftikhar, Sadaf; Bajwa, Ahmed Fayyaz; Baloch, Tauseef Ahmed (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the prevalence of restless leg syndrome in patients with spinal cord injury using a consensus criterion. Method: The cross-sectional study was conducted from November 29, 2018, to February 28, 2021 at the departments of Neurology and Orthopaedic Surgery, King Edward Medical University, Mayo Hospital, Lahore, Pakistan, and comprised patients of either gender aged 18-80 years having spinal cord injuries. All the patients were interviewed using a 10-item questionnaire, and were assessed using the five-point consensus criteria of the International Restless Leg Syndrome Study Group. Data was analysed using SPSS 20. Results: Of the 253 patients, 128(50.6%) were males and 125(49.4%) were females. The overall mean age was 38.6±14.2 years. Restless leg syndrome was present in 116(45.8%) patients, and 64(55.2%) of them were males (p>0.05). The mean duration of the symptoms was 18.9±16.9 months. Causes of spinal cord injury included metastasis 28(11.1%) multiple sclerosis 32(12.6%), neuromyelitis optica spectrum disorders 68(26.9%), tuberculous spondylitis 85(33.6%), trauma 24(9.5%) and viral myelitis 16(6.3%). Conclusion: Restless leg syndrome was prevalent in less than half the patients having spinal cord injury. It was more prevalent in males compared to females, but the difference was not significant. Key Words: Restless leg syndrome, Spinal cord injury, Leg pain syndrome.